2013
DOI: 10.1177/1479972312471548
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and providers’ perceptions of the impact of health literacy on communication in pulmonary rehabilitation

Abstract: Chronic obstructive pulmonary disease (COPD) is the most prevalent form of chronic respiratory diseases worldwide. Pulmonary rehabilitation, including self-management education, highlights the importance of good patient-provider communication in establishing optimal care. There is a growing awareness of the potential impact of health literacy (HL) on the patients' access to and understanding of medical information. This study was designed to explore the patients' and health care professionals' (HCPs) perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 27 publications
2
61
0
Order By: Relevance
“…Alternatively, the modest improvements noted in some studies may be related to the patients' level of literacy. [21][22][23][24] Although our booklet used simple language, 53.3% of the patients in the intervention group had not completed high school and may have found the content difficult. Literacy carries a stigma and therefore patients may not have identified a lack of understanding of the material provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the modest improvements noted in some studies may be related to the patients' level of literacy. [21][22][23][24] Although our booklet used simple language, 53.3% of the patients in the intervention group had not completed high school and may have found the content difficult. Literacy carries a stigma and therefore patients may not have identified a lack of understanding of the material provided.…”
Section: Discussionmentioning
confidence: 99%
“…Literacy carries a stigma and therefore patients may not have identified a lack of understanding of the material provided. 22,23 Eighty-seven percent (n=13) of the patients reported that nothing was required to improve the program. Although the intervention group included a higher proportion of patients with a low level of education, the increase in BCKQ suggests that the intervention adequately targeted patients who may have had low health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…The existing body of work has documented a strong relationship between health literacy and health outcomes for adults, 1 and a growing number of studies have examined health literacy for parents, finding that low health literacy among parents leads to worse child health outcomes. 2 In particular, research has found that health literacy, including numeracy, can play an important role for communication in health care settings 36 ; people with lower health literacy skills often report greater issues with provider communication.…”
Section: Introductionmentioning
confidence: 99%
“…The study also highlights the perceived barriers towards HL and unlike other studies, time constraint was not regarded as the main obstacle in practicing and applying HL skills. This study identifies the ‘lack of knowledge’ and ‘lack of organizational resources as the major barriers to HL among the community pharmacists.…”
Section: Discussionmentioning
confidence: 53%
“…The concept of HL not only includes improving their level of literacy about diseases, medicines and self‐care but it starts at identifying the literacy needs or the areas that need to be addressed predominantly. Considering the definition of HL by WHO and the relevant literature, HL is the shared responsibility of healthcare providers as well as patients …”
Section: Discussionmentioning
confidence: 99%